Kissing Bugs in the United States: Risk for Vector-Borne Disease in Humans - Stephen A. Klotz; Patricia L. Dorn; Mark Mosbacher; Justin O. Schmidt (SAGE Publishing, 2014)
Eleven species of kissing bugs are found in the United States. Their home ranges may be expanding northward, perhaps as a consequence of climate change. At least eight of the species, perhaps all, are reported to harbor Trypanosoma cruzi , the parasite that causes Chagas disease. Because humans are encroaching on kissing bug habitat, there is concern for vector-transmitted Chagas disease in the United States. To date, documented autochthonous cases of Chagas in humans in the United States are rare. Kissing bugs are capable of adapting to new habitats such as human domiciles; however, they do not colonize homes in the United States as in Central and South America. We review the biology, behavior, and medical importance of kissing bugs and the risk they pose for transmission of Chagas disease in the United States. Where possible, descriptions of US species are compared to the epidemiologically important Latin American species.